Arttaste. - Hoet, Jan (Gent : Toohcsmi Uitgevers Gent, 2005)
De Beukelaer, Sergio ; Bijl, Guillaume ; Bogaert, Thomas ; Borremans, Michaël ; Braeckman, Dirk ; Brusselmans, Ellen ; Chiasera, Paolo ; Colson, Vaast ; Copers, Leo ; De Cordier, Louis ; De Cupere, Peter ; DC, Franky ; Dedobbeleer, Koenraad ; Delrue, Ronny ; Delvoye, Wim ; Deprez, Dany ; Devriendt, Robert ; Dheedene, Stefaan ; Geers, Kendell ; Van Imschoot, Jan ; Kobayashi, Masato ; van Lieshout, Joep ; Lopez Menchero, Emilio ; Martin, Kris ; McCarthy, Caroline ; Van Mechelen, Koen ; Meuris, Wesley ; Muller, Fien ; Ntakiyica, Aimé ; Op de Beeck, Hans ; Peinado, Bruno ; Provost, Nicolas ; Robijns, Gert ; Ronsse, Matthieu ; Tahon, Johan ; Vanseveren, Hannes ; Verhulst, Nicolas ; Vermeersch, Pieter ; Wauman, Andy
boek